The Educational Context In The Literature Of Ibn Al-Muqaffa Through His Book Al-Adab Al-Saghir/ السياق التربوي في أدب ابْنِ الْمُقَفَّع من خلال كتابه الْأدب الصغير - Almaghzwi, Adel (Ijaz Arabi Journal of Arabic Learning, 2024)
The purpose of this study is to analyze the contents of the book "Al-Adab Al-Shaghir" by the author Abdullah Ibn Al-Muqaffa, and identify the educational context of the texts of this book. This study uses an inductive approach to extrapolate Arabic texts and extract research materials and descriptive-analytical (content analysis) To analyze. The author focuses on social behavior and discusses topics including the importance of self-discipline and self-control and the importance of friendship and positive social relationships. It also emphasizes ethical behavior and the importance of moral values, personal relationships, and social responsibility. He discusses educational issues with reason, wisdom, and literature, which increases the influence of his philosophy on readers and contributes to establishing educational values in society. The study results also show that the content and values of education, the most prominent of which are the love of knowledge, choosing good friends, Honesty and integrity, and their role in encouraging personal and social growth, Self-awareness, and self-control. This book contains many rhetorical methods with the educational implication that a wise person must be at odds with himself and judge himself. Among the most prominent educational means in Ibn al-Muqaffa's texts are education by example, the need for ethics and discipline (education) and its role in the context of watering the mind, and developing society to benefit from these contents in raising children in the current era, and it is recommended that these values need to be included in educational books so that pre-university students can contribute to instilling values and purifying the minds of the younger generation.